A Comparison of Fiqih on Profit Sharing of Investments in the Agricultural Sector - Prasetio, Andri; Setiawan, Iwan; Jubaedah , Dedah (Zona Law And Public Administration Indonesia, 2025)
This article explains the Muzara'ah, Mukhabarah, and Musaqah contracts. These are forms of agricultural cooperation that have existed since ancient times. In practice, the current collaboration between landowners and cultivators is commonly referred to as paroan sawah (rice paddy), where the contract is not written but only verbal. This often results in losses due to the lack of authentic evidence. In Islamic banking, the most widely used principles are musyawarah and mudharabah. Muzara'ah is specifically used by some Islamic banks for plantation or agricultural financing. Muzara'ah originates from the concept of "passing". Due to this specific nature of muzara'ah, most Islamic banks use musyawarah or salam for agricultural credit. However, over time, the practice of muzara'ah has tended towards mudharabah (profit-sharing cooperation). Technically, mudharabah is a business cooperation contract between two parties, where one party (the shahib al maal) provides all the capital, while the other party, known as the mudharib, manages the business. Profits in mudharabah are shared according to the agreement outlined in the contract, while losses are borne by the negligent party. Keywords: Muzara'ah contract, Mukhabarah, Musyaqoh